Adolescent short video addiction in China: unveiling key growth stages and driving factors behind behavioral patterns - Guo, Jiaxiang; Chai, Ran (Frontiers in Psychology, 2024)
The proliferation of short video apps has brought to the forefront the issue of ado-lescent addiction, a challenge that resonates across Chinese society. Despite growing attention, a comprehensive understanding of the factors propelling addiction at various adolescent stages and its impact on academic performance remains scarce. This study aims to fill this void by identifying key growth stages and crafting targeted intervention strategies. Our investigation en-gaged 1,896 Chinese students, averaging 15 years old, at pivotal educational junctures. Employing a mixed-method approach, we utilized interviews and surveys, enhanced by fixed effects models and instrumental variables, to discern patterns in short video addiction. The study re-vealed stage-specific catalysts for addiction: social identity in junior high, academic stress in senior high, and personality traits in university students. A concerning trend was the double and triple rate of severe addiction among senior high students compared to their junior high and university counterparts, respectively, with a peak of 52.7% mild addiction in university. Our predictive model provides a holistic perspective on the drivers of addiction. This groundbreaking analysis delineates the complex interplay of adolescent short video addiction in China, under-scoring its profound implications for academic progression in senior high. The findings under-score the urgent need for tailored interventions to counteract the adverse effects of addiction.